Archeologiczne badania weryfikacyjne kopca w miejscowości Leśno, gm. Brusy - Walenta, Krzysztof; Wójcik, Andrzej (Acta Universitatis Lodziensis. Folia Archaeologica, 1989)
The mound with situated on it an old manor of Sikorski family was the subject of verifying studies. The mound is of an oval shape with the basis of 60x100 m and plateau of 46x55 m. The shape of the mound allows to suppose that it could have been used as an early mediaeval castle (made of wood and earth), mediaeval or contemporary fortified abode. Such suggestions are confirmed by archaeological and historical sources. The first mention about Leśno comes from 1354 when Leśno (Leysten) was granted to Ditrik von Leysten by the Grand Master Winrik von Kniprode. Archaeological sources found during the research came mostly from the XIIIth century although there are among them some fragments of hand-made utensils which may date back to the beginnings of the XIIIth century. Thus, they indicate on the settlement much earlier to that which so far has been confirmed by historical sources. Achieved results do not enable us to determine the character of the settlement unmistakably. This problem can only be solved by stationary investigations which are planned for the future.